2002
DOI: 10.1002/cne.10259
|View full text |Cite
|
Sign up to set email alerts
|

Red nucleus projections to distinct motor neuron pools in the rat spinal cord

Abstract: Despite being one of the more extensively investigated descending pathways of the rat spinal cord, the termination pattern and postsynaptic targets of the rubrospinal tract (RST) still present some unresolved issues. In addition to locomotor functions, the RST is implicated in the control of limb movements such as reaching and grasping. Although a strong RST projection onto interneurons of intermediate Rexed's laminae V and VI have been described through the entire length of the rat spinal cord, the existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 48 publications
6
80
1
Order By: Relevance
“…The HY TME agent is transported within the CNS via three descending motor tracts (5). These motor tracts either directly synapse on VMNs or synapse on interneurons that (1,9,23,24). Consistent with this finding, HY TME PrP Sc is first detected in VMNs of the lumbar spinal cord ipsilateral to the site of inoculation.…”
Section: Discussionsupporting
confidence: 53%
“…The HY TME agent is transported within the CNS via three descending motor tracts (5). These motor tracts either directly synapse on VMNs or synapse on interneurons that (1,9,23,24). Consistent with this finding, HY TME PrP Sc is first detected in VMNs of the lumbar spinal cord ipsilateral to the site of inoculation.…”
Section: Discussionsupporting
confidence: 53%
“…Vestibular signals participate in regulating hindlimb blood flow (20,22,41), and thus the infected neurons in the lateral vestibular nucleus likely are components of the neural pathway that mediates this response. The red nucleus is not typically considered to participate in autonomic regulation but instead plays a fundamental role in motor control in the rat (13,24). Red nucleus neurons could potentially contribute to altering limb blood flow in parallel with movement and thus may comprise elements in the neural circuit underlying central command (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VGluT-1 expression was specifically detected in cells of the gigantocellular reticular nucleus (38). Red nucleus and brainstem neurons extend their axons along the lateral white matter of the spinal cord to form rubrospinal, reticulospinal, and vestibulospinal tracts (18,(39)(40)(41). We found that a number of these neurons were retrogradely labeled by CT␤ application at the muscular synaptic terminals of the grafted nerve, demonstrating they were primarily involved in the new glutamatergic innervation of obliquus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The retrograde tracing in the regenerated nerve was performed by injecting the cholera toxin ␤-subunit (CT␤, 1 mg͞ml, List Biological Laboratories, Campbell, CA) into the reinnervated obliquus muscle (18). Six days later, the animals were perfused, and CT␤ was immunodetected in sections from brain and spinal cord by using the anticholeragenoid antibody (1:4,000; List Biological Laboratories).…”
Section: Methodsmentioning
confidence: 99%